A Survey on Multilevel Data Security Framework for Cloud Data - Prajwal V1, Mohan Kumar T. G2, Sanjay H. A3, Manish S Byatroy4, Yashaswi S5, Niharika Ganesh (International Journal of Advanced Science and Technology, 2020)
Cloud computing is one of the domains in which rapid growth is taking place. This domain has a high demand in the current society as it offers a wide range of services to the users through the Internet. The security of data is being one of the major concerns in the cloud. RSA algorithm provides security for the data but fails in some aspects such as speed as it is slow when it needs to encrypt huge data. And also requires third party to verify the reliability of keys. The proposed RMAD framework which uses ABE, provides better security using multiple algorithms like RSA ,Genetic and MD5.